The role of antioxidant phytonutrients in the prevention of diseases - Lugasi, Andrea (Acta Biologica Szegediensis, 2003)
The authors investigated the in vitro antioxidant properties of nine selected flavonoid aglycons, namely quercetin, kaempferol, myricetin, apigenin, luteolin, daidzein, genistein, formononetin and biochanin A. The in vitro antioxidant power of flavonoids basically depends on their chemical structure. The concentration of those flavonoids in vegetables and fruits frequently consumed in Hungary was examined by a RP-HPLC method. Referring to the total flavonoid content, rich sources were onions, parsnip, spinach, different parts of celery, and lentils. Among the fruits berries were very rich sources of flavonoids (blackberry, red current). The flavonoid intake was estimated in two groups, first included more than 500 schoolboys and girls aged 12-15 years, and the second group was about 200 healthy adults aged 25-60 years. The average dietary flavonoid intake of the children and the adults was 19.5±26.6 and 18.8±28.9 mg/day, respectively. The flavonoid intake showed high differences among the subjects. The consumption of flavonoids in the children’s group was from 0 to 179 mg/day, and in the adults group from 0.5 to 310 mg/day. Although two groups in our study did not represent exactly the total Hungarian population it is supposed that the average daily flavonoid intake of the population is not different from these data. The estimated Hungarian intake is very similar to that of others published in the literature.